Ambulatory blood pressure adds little to Framingham Risk Score for the primary prevention of cardiovascular disease in older men: secondary analysis of observational study data. Issue 9 (8th September 2014) - Bell, Katy J L; Beller, Elaine; Sundström, Johan; McGeechan, Kevin; Hayen, Andrew; Irwig, Les; Neal, Bruce; Glasziou, Paul
Abstract : Objective: To determine the incremental value of ambulatory blood pressure (BP) in predicting cardiovascular risk when the Framingham Risk Score (FRS) is known. Methods: We included 780 men without cardiovascular disease from the Uppsala Longitudinal Study of Adult Men, all aged approximately 70 years at baseline. We first screened ambulatory systolic BP (ASBP) parameters for their incremental value by adding them to a model with 10-year FRS. For the best ASBP parameter we estimated HRs and changes in discrimination, calibration and reclassification. We also estimated the difference in the number of men started on treatment and in the number of men protected against a cardiovascular event. Results: Mean daytime ASBP had the highest incremental value; adding other parameters did not yield further improvements. While ASBP was an independent risk factor for cardiovascular disease, addition to FRS led to only small increases to the overall model fit, discrimination (a 1% increase in the area under the receiver operating characteristic (ROC) curve), calibration and reclassification. We estimated that for every 10 000 men screened with ASBP, 141 fewer would start a new BP-lowering treatment (95% CI 62 to 220 less treated), but this would result in 7 fewer cardiovascular events prevented over the subsequent 10 years (95% CI 21 fewer events prevented to 7 more events prevented). Conclusions: In addition to a standard cardiovascular risk assessment it is not clear that ambulatory BP measurement provides further incremental value. The clinical role of ambulatory BP requires ongoing careful consideration.